Control of Trustee Discretion: The Rule in Re Hastings-Bass - Simon Kerry (UCL Journal of Law and Jurisprudence, 2015)
This article examines the Court of Appeal decision in Pitt v Holt, and its implications for the rule in Re Hastings-Bass. The article argues that there are some inconsistencies between the post-Pitt position and other rules relating to the control of trustee discretion, particularly fraud on a power and the standing of trustees to sue in respect of their own breaches of trust. It also considers what is meant by saying a power is 'fiduciary', and argues that it is wrong to categorise the duty created by Pitt as fiduciary, as the Court of Appeal appears to do. Finally, it considers the reasons why settlors may wish to restore the pre-Pitt position by careful drafting, and presents a possible strategy by which they might do so. Read more